The Impact of social media on Learning English Vocabularies - Sidig Sidgi, Dr. Lina Fathi (International Journal of Humanities and Education Development (IJHED), 2021)
Social media usage has been on the rise in last eight years. Different fields, including business, politics, social events, and education have reaped big from social media. However, the use of social media on language learning has been under-researched. As a result, the sole focus of the research paper was to explore the impact of social media on learning English vocabulary. A systematic review of the literature methodology was utilized. The analysis discovered that social media is an important learning tool. It provides motivation, engagement, and exposure to a wide range of English vocabularies, improving the learner's language skills. As a result, social media has been depicted as a valuable tool that modern-day teachers and curriculum developers should consider in their lesson planning and language acquisition teaching.